Adaptation of the Australian Palliative Care Phase concept to the German palliative care context: a mixed-methods approach using cognitive interviews and cross-sectional data - Lehmann, Eva; Hodiamont, Farina; Landmesser, Mirjam; Knobloch, Carina; Nauck, Friedemann; Ostgathe, Christoph; Gruene, Bettina; Bausewein, Claudia (BMC Palliative Care, 2021)
Background: Palliative care phases (stable, unstable, deteriorating, terminal and bereavement) are routinely used in Australia and the UK to describe the clinical situation of patients and their families and to evaluate the associated care plan. In addition, it serves as a benchmark developed by the Australian Palliative Care Outcome Collaboration (PCOC) and is used nationwide for comparisons between services. In Germany, the concept is not used consistently due to various translations. Furthermore, there is no nationwide systematic approach to routinely assess clinical outcomes in palliative care. The study aims to develop a German version of the palliative care phase definitions by adapting them culturally, and to examine the inter-rater reliability of the adjusted definitions with healthcare professionals. Methods: Mixed-methods approach: Cognitive interview study using ‘think aloud’ and verbal probing techniques and a consecutive multi-center cross-sectional study with two clinicians independently assigning the phase definitions. Interviewees/participants were selected through convenience and purposive sampling in specialist palliative care inpatient units, advisory and community services and in three specialist palliative care units with doctors, nursing staff and allied health professionals. Results: Fifteen interviews were conducted. Identified difficulties were: Some translated terms were 1) not self-explanatory (e.g. ‘family/carer’ or ‘care plan’) and (2) too limited to the medical dimension neglecting the holistic approach of palliative care. (3) Problems of comprehension regarding the concept in general occurred, e.g. in differentiating between the ‘unstable’ and ‘deteriorating’ phase. Inter-rater reliability was moderate (kappa = 0.44; 95% CI = 0.39–0.52). The assignment of the phase ‘deteriorating’ has caused the most difficulties. Conclusion: Overall, the adapted palliative care phases are suitable to use in the German specialist palliative care setting. However, the concept of the phases is not self-explanatory. To implement it nationwide for outcome measurement/benchmarking, it requires further education, on-the-job training and experience as well as the involvement of healthcare professionals in implementation process. For the use of international concepts in different healthcare systems, a deeper discussion and cultural adaptation is necessary besides the formal translation.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Cognitive interviewing; Inter-rater reliability; Outcome measurement; Palliative care; Palliative care phases; Quality of healthcare; Reproducibility of results

Detection of pre-existing neutralizing antibodies against Ad26 in HIV-1-infected individuals not responding to the Ad26.COV2.S vaccine - Schmidt, Katja; Harrer, Ellen; Schönau, Verena; Simon, David; Kleyer, Arnd; Steininger, Philipp; Korn, Klaus; Schett, Georg; Knobloch, Carina; Nganou-Makamdop, Krystelle; Harrer, Thomas (Infection, 2023)
Purpose: The Ad26.COV2.S vaccine is a replication-incompetent human adenovirus type 26 vector encoding the SARS-CoV-2 spike protein. In a phase 1-2a trial, a single dose of Ad26.COV2.S induced SARS-CoV-2 spike-specific antibodies in ≥ 96% of healthy adults. To investigate vaccine immunogenicity in HIV-1-infection, we measured SARS-CoV-2 spike-specific antibodies in Ad26.COV2.S vaccinated HIV-1-infected patients and analyzed the presence of pre-existing Ad26 neutralizing antibodies. Methods: We included all Ad26.COV2.S vaccinated HIV-1-infected patients of Erlangen HIV cohort fulfilling all inclusion criteria. The study cohort consisted of 15 HIV-1-infected patients and three HIV-1-uninfected subjects who received the Ad26.COV2.S vaccine between April and November 2021. Pre-vaccination sera were collected between October 2014 and June 2021, post-vaccination sera between June and December 2021. Neutralizing antibodies towards Ad26 were determined by a FACS-based inhibition assay measuring the expression of SARS-CoV-2 spike and adenoviral proteins in HEK293T cells after in-vitro transduction with Ad26.COV2.S or the control ChAdOx1-S. Results: Six out of 15 HIV-1-infected patients failed to develop SARS-CoV-2-specific antibodies and four patients developed weak antibody responses after vaccination with Ad26.COV2.S. Pre-vaccination sera of four of the six vaccine non-responders showed neutralizing activity towards Ad26.COV2.S but not toward the ChAdOx1-S vaccine at 1:50 dilution. After Ad26.COV2.S vaccination, 17 of the 18 subjects developed strong Ad26-neutralizing activity and only one of the 18 subjects showed neutralizing activity towards the ChAdOx1-S vaccine. Conclusion: Ad26.COV2.S vaccination showed a high failure rate in HIV-1-infected patients. Pre-existing immunity against Ad26 could be an important contributor to poor vaccine efficacy in a subgroup of patients.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Ad26.COV2.S; Adenovirus 26; HIV-1; Neutralizing antibodies; SARS-CoV-2; SARS-CoV-2 vaccine

Homologous COVID-19 BNT162b2 mRNA Vaccination at a German Tertiary Care University Hospital: A Survey-Based Analysis of Reactogenicity, Safety, and Inability to Work among Healthcare Workers - Niekrens, Valentin; Esse, Jan; Held, Jürgen; Knobloch, Carina; Steininger, Philipp; Kunz, Bernd; Seggewies, Christof; Bogdan, Christian (Vaccines, 2022)
At the start of the SARS-CoV-2 pandemic, healthcare workers had an increased risk of acquiring coronavirus disease (COVID)-19. As tertiary care hospitals are critical for the treatment of severely ill patients, the University Hospital Erlangen offered BNT162b2 mRNA vaccination against COVID-19 to all employees when the vaccine became available in Germany. Here, we performed a survey to assess the age- and sex-dependent reactogenicity and safety of BNT162b2 in a real-life setting with a special emphasis on the rate of vaccine-related incapacity to work amongst the employees. All vaccinated employees were invited to participate in the survey and received access to an electronic questionnaire between 31 March and 14 June 2021, which allowed them to report local and systemic adverse effects after the first or second vaccine dose. A total of 2372 employees completed the survey. After both the first and second dose, women had a higher risk than men for vaccine-related systemic side effects (odds ratio (OR) 1.48 (1.24-1.77) and 1.49 (1.23-1.81), respectively) and for inability to work (OR 1.63 (1.14-2.34) and 1.85 (1.52-2.25), respectively). Compared to employees >= 56 years of age, younger vaccinated participants had a higher risk of systemic reactions after the first (OR 1.35 (1.07-1.70)) and second vaccination (OR 2.08 (1.64-2.63)) and were more often unable to work after dose 2 (OR 2.20 (1.67-2.88)). We also recorded four anaphylactic reactions and received two reports of severe adverse effects indicative of vaccine complications. After the first and second vaccination, 7.9% and 34.7% of the survey participants, respectively, were temporarily unable to work, which added up to 1700 days of sick leave in this cohort. These real-life data extend previous results on the reactogenicity and safety of BNT162b2. Loss of working time due to vaccine-related adverse effects was substantial, but was outweighed by the potential benefit of prevented cases of COVID-19.
CRIS-Team WoS Importer:2022-06-10